In vitro slow-release urea characteristics under different molasses levels contained in rice straw based diets - Kardaya, D.; Wiryawan, K.G.; Parakkasi, A.; Winugroho, H.M. (Indonesian Animal Sciences Society, 2009)
Slow-release urea characteristics of zinc-urea, zeolites-urea, and zeolites-zinc-urea were examined using in vitro techniques. The objective of this experiment was to study the in vitro slow-release urea characteristics of zinc-urea, zeolites-urea, and zeolites-zinc-urea under different molasses concentrations in relation to the ruminal fermentative changes observed in different incubation time. The experimental design employed was randomized block design with a 4 x 3 factorial arrangement plus a control treatment, and conducted in two replications. Factors were various urea sources (urea, zinc-urea, zeolites-urea, and zeolites-zinc-urea) and molasses concentrations (0%, 6%, and 12%) in rice straw based diets. The control treatment was rice straw based diet containing neither urea nor molasses. Diets consisted of 45% rice straw and 55% concentrates (DM basis) were formulated to have similar N and TDN levels. Responses of parameters measured were subjected to MANOVA using the GLM procedure of SPSS 16.00 and differences among mean values, if applicable, were examined using HSD-test. Orthogonal comparisons were used to determine the effects of control treatment vs. various urea sources following significance for the two-factor ANOVA model. Results indicated that zinc-urea, zeolites-urea, and zeolites-zinc-urea under different molasses concentrations contained in rice straw based diets decreased ruminal ammonia up to 48 hours incubation, controlled total VFA level and pH values revealed from lower NH3:VFA ratio, and improved both in vitro dry matter and organic matter degradabilities. The best impact of the in vitro slow-release urea characteristics of zinc-urea, zeolites-urea, and zeolites-zinc-urea on the ruminal fermentative changes (NH3, VFA, pH, DMD, OMD) was well attributed to the diets contained 6% molasses. Key words: Slow-Release Urea, Molasses, Rice Straw, In Vitro